2018
DOI: 10.17503/agrivita.v40i0.1715
|View full text |Cite
|
Sign up to set email alerts
|

Internal Versus Edge Row Comparison in Jajar Legowo 4:1 Rice Planting Pattern at Different Frequency of Fertilizer Applications

Abstract: Jajar legowo 4:1 cropping pattern has been adopted by rice farmers; however, there has been limited information on the comparison between internal and edge rows. In addition, the effects of timing and frequency of fertilizer applications on rice cultivated at riparian wetland also have to be understood. In this research, both single and split applications of fertilizer were employed. The single fertilizer applications were applied at 15 days after transplanting (DAT) (T1), 30 DAT (T2), 45 DAT (T3); and the spl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…The effect of priming treatment on rice vegetative growth was mainly exhibited on development of tillers. Number of tillers is important since it determines number of panicles produced and potential yield in rice crop (Kartika et al, 2018a). Higher number of tillers was produced in hydro-priming treatment compared to osmo-priming with 10% to 20% PEG concentrations (Figure 1).…”
Section: Carry-over Effects Of Seed Priming On Vegetative Growthmentioning
confidence: 99%
“…The effect of priming treatment on rice vegetative growth was mainly exhibited on development of tillers. Number of tillers is important since it determines number of panicles produced and potential yield in rice crop (Kartika et al, 2018a). Higher number of tillers was produced in hydro-priming treatment compared to osmo-priming with 10% to 20% PEG concentrations (Figure 1).…”
Section: Carry-over Effects Of Seed Priming On Vegetative Growthmentioning
confidence: 99%
“…Lakitan et al (2018) found that number of leaves at late vegetative growth stage was higher in rice plants grown on biochar-treated soil. Kartika et al (2018a) also reported that biochar affected leaf area ratio. Moreover, there were significantly higher leaf area index in rice plants at edge rows compared to those at internal rows in 4:1 Jajar-Legowo planting system (Kartika et al, 2018b).…”
Section: No Effect Of Substrate On Number Of Seedling Leavesmentioning
confidence: 92%
“…Local farmers very rarely grow rice twice per year. Therefore, cropping intensity is low (Kartika et al, 2018a). Rice growing season at this ecosystem is started after floodwater has subsided to less than 15 cm and harvested during dry season (Lakitan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, minor adjustment in agricultural practices, without any significant additional cost for inputs, can increase yield. Kartika et al (2018) reported that planting pattern and split N fertilizer application increased leaf chlorophyll and nitrogen content during vegetative stage and yield in rice cultivated at riparian wetlands. Increase in rice yield was also reported by Cahyono & Hartati (2013) if P fertlitizer was splitted into two or three times of application.…”
Section: Affordable Technologies and Their Impactsmentioning
confidence: 99%